The Effects of Reading On Writing: A Study on Sixth Form Students of Sekolah Menengah Tinggi Kajang - Kuek, Mamour Choul Turut (1999)
A quasi-experimental study was conducted to test the hypotheses that teaching reading and writing integratively in the ESL classroom enhances students' intellectual processes and their syntactical maturity in writing more than the teaching of these two skills separately. The subjects of this study comprise 43 Form 6 students of Sekolah Menengah Kebangsaan Tinggi Kajang, a high school in the suburb of Kuala-Lumpur, Malaysia. Out of a total of six classes, two classes were randomly selected, one Science class and the other an Arts class. Each group was left intact in their own class. In both classes, English was taught as a subject. The subjects were given writing tests before the start of the study. Then the two classes were clustered randomly assigned into experimental and control group. The experimental group was taught reading and writing integratively while the control group was taught reading and writing separately. At the end of the study the two groups were post-tested. The findings showed that the integrative teaching of reading and writing enhances students' syntactical maturity in writing (t =2.110, df = 36, P <0.05). The findings also showed that integrative teaching of reading and writing enhances students' intellectual processes in writing. The study suggested that reading and writing should be taught integratively in ESL classrooms.